Effect of rice glutelin-resveratrol interactions on the formation and stability of emulsions: A multiphotonic spectroscopy and molecular docking study. (December 2019) - Dai, Taotao; Li, Ruyi; Liu, Chengmei; Liu, Wei; Li, Ti; Chen, Jun; Kharat, Mahesh; McClements, David Julian
Abstract: An understanding of the molecular mechanisms underpinning protein-polyphenol interactions is critical for incorporating bioactive polyphenols into functional foods and beverages. This study characterized the interaction between rice glutelin (RG) and resveratrol (RES) using a combination of spectroscopic and molecular simulation techniques. Resveratrol quenched the intrinsic fluorescence of rice glutelin, which is indicative of a binding interaction between the two molecules. Resveratrol addition caused a decrease in surface hydrophobicity, alteration in protein microenvironment, and change in conformation of the rice glutelin. Thermodynamic analysis suggested that the binding of resveratrol to the protein was spontaneous and mainly driven by hydrophobic interactions. A RG-RES complex with a molar ratio of 1:1 was formed, suggesting that rice glutelin may be a suitable carrier for resveratrol. More detailed insights into the nature of the binding site and the forces involved were obtained using molecular simulation studies. Finally, we examined the impact of resveratrol on the formation and stability of oil-in-water emulsions stabilized by rice glutelin. Emulsions containing small highly anionic oil droplets could be formed in the presence of resveratrol, but a population of large particles was observed during storage. These particles appeared to consist of oil droplets with water droplets trapped inside. We hypothesize that water diffused into the oil droplets and formed small water droplets that were stabilized by amphiphilic resveratrol. Our results have important implications for the development of effective delivery systems for resveratrol. Graphical abstract: Image 1 Highlights: Resveratrol (RES) changes the conformation and surface hydrophobicity of rice glutelin (RG). The major RG-RES interaction was a hydrophobic interaction. A spectroscopy-binding molecular simulation was used to explore the interaction mechanism. The formation of a RG-RES complex did not adversely the stability of RG emulsions.